2015
DOI: 10.1016/j.brat.2015.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Does Stepping Stones Triple P plus Acceptance and Commitment Therapy improve parent, couple, and family adjustment following paediatric acquired brain injury? A randomised controlled trial

Abstract: Parent skills training and ACT may be efficacious in improving parent, family, and couple outcomes in families of children with an ABI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
111
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(119 citation statements)
references
References 34 publications
5
111
0
3
Order By: Relevance
“…This poor response rate was symptomatic of the few studies to collect data at the 6-month follow-up interval. The two articles reporting on the study by Brown et al 128,140 performed similarly to the Whittingham articles. The article by Reigada et al 125 was also rated as being at low risk of bias overall, with only two negative scores.…”
Section: Reviewmentioning
confidence: 77%
See 3 more Smart Citations
“…This poor response rate was symptomatic of the few studies to collect data at the 6-month follow-up interval. The two articles reporting on the study by Brown et al 128,140 performed similarly to the Whittingham articles. The article by Reigada et al 125 was also rated as being at low risk of bias overall, with only two negative scores.…”
Section: Reviewmentioning
confidence: 77%
“…118,119,[123][124][125][126][127][128][130][131][132][133][134]137,138 Five included studies were reported in more than one included journal article reporting on different study details or findings. Brown et al 140 reported additional parent and family function outcomes from their 2014 trial. 128 We excluded one article associated with this study as it did not provide any effectiveness outcomes that were not seen in the previous articles.…”
Section: Descriptive Statisticsmentioning
confidence: 99%
See 2 more Smart Citations
“…The aim of acceptance and commitment therapy is to decrease experiential avoidance (experiential avoidance, attempt to adjust or control unwelcome inner experiences of cognitions, memories or feelings) and foster mental flexibility that is the ability of flexible communicating with internal experiences and adaptive responses to the situations for the worthwhile purpose of life. 2 There is empirical support for the effectiveness of acceptance and commitment therapy on the treatment of psychological distress. 3 Acceptance and commitment therapy is the third wave therapy behavior.…”
Section: Introductionmentioning
confidence: 99%